F-027EXPLORING STAGE I NON-SMALL-CELL LUNG CANCER: DEVELOPMENT OF A PROGNOSTIC MODEL PREDICTING 5-YEAR SURVIVAL. (June 2014) - Guerrera, Francesco; Errico, L.; Evangelista, A.; Bora, G.; Lisi, E.; Olivetti, S.; Asteggiano, E.; Filosso, P.L.; Ardissone, F.; Oliaro, A.
Abstract : Objectives: In the last years, impressive results in diagnosis and treatment of non-small-cell lung cancer (NSCLC) were accomplished. In spite of that, more than 30% of patients with Stage I NSCLC die at 5 years from surgical treatment. Defining prognostic factors to identify patients with a poor prognosis and develop tailored treatment strategies is then mandatory. The aim of our study is to design a model able to define prognosis in patients with Stage I NSCLC, submitted to surgery with curative intent. Methods: A retrospective analysis of two surgical registries was performed. Overall survival (OS) was calculated starting from the date of surgery. Predictors of OS were investigated using the Cox model with shared frailty (accounting for the within-center correlation). Candidate predictors were: age, gender, smoke habit, morbidity, previous malignancy, ECOG PS, cN, SUVmax, FEV1, TLCO, vascular invasion, systematic lymphadenectomy, pT, histology, surgical resection type. In the final model were included predictors with P ≤ 0.15, after a backward selection. Missing data in evaluated predictors were multiple-imputed and combined estimates were obtained from 5 imputed datasets. Results: Analyses were performed on 943 patients from two institutions. Median follow-up was 48 months. Two hundred and twenty-one patients died, with a 5-year OS of 75%. Final Cox model demonstrated that mortality was positively associated with male gender, vascular invasion, pT, cardiac comorbidities, systematic lymphadenectomy, TLCO and histology. The final model showed a fair discrimination ability with a C-statistic equal to 0.701: the calibration of the model indicated a good agreement between observed and predicted survival in poor prognosis patients. Conclusions: We design an encouraging prognostic model based on clinical, pathological and surgical data, easy to draw out from routine practice. Further directions will be refining and validating our prognostic model, providing an easy to use prognostic tool for Stage I NSCLC patients. Disclosure: No significant relationships.